Circulating Interleukin-6 is a biomarker for coronary atherosclerosis in nonalcoholic fatty liver disease: Results from the Multi-Ethnic Study of Atherosclerosis. (15th May 2018) - Simon, Tracey G.; Trejo, Maria Esther Perez; McClelland, Robyn; Bradley, Ryan; Blaha, Michael J.; Zeb, Irfan; Corey, Kathleen E.; Budoff, Matthew J.; Chung, Raymond T.
Abstract: Background: Biomarkers to predict the presence and severity of subclinical cardiovascular disease (CVD) in nonalcoholic fatty liver disease (NAFLD) are lacking. Methods: 3876 participants from the Multi-Ethnic Study of Atherosclerosis (MESA), without known chronic liver disease underwent baseline non-contrast cardiac CT, with NAFLD defined by validated liver:spleen ratio (L:S) < 1.0, and subclinical CVD defined by coronary artery calcium (CAC) score > 0. Randomly-selected subgroups underwent detailed inflammatory marker testing, including LpPLA2 mass (N = 2951), activity (N = 3020), high-sensitivity C-reactive protein (hsCRP; N = 3849), and interleukin-6 (IL-6; N = 3764). Among those with NAFLD, we estimated the prevalence of CAC > 0 and CAC > 100 for each SD biomarker increase, using multivariable log-binomial regression models adjusted for cardiometabolic risk factors. Results: Seventeen percent (N = 668) of participants met the criteria for NAFLD. NAFLD participants were younger (mean age 61 ± 10 vs. 63 ± 10 years, p < .0001) but more likely to have an elevated BMI (mean 31.1 ± 5.5 vs. 28.0 ± 5.2 kg/m 2, p < .0001), diabetes (22% vs. 11%, p < .0001), and increased inflammatory biomarkers, including LpPLA2 activity, hsCRP and IL-6 (all p < .0001). Among NAFLD participants, IL-6 was the only biomarker independently associated with prevalent CAC > 0 (PR = 1.06 [1.00–1.11]), or CAC > 100 (PR = 1.09 [1.02–1.17]). In contrast, circulating LpPLA2 mass/activity and hsCRP were not associated with either the prevalence or severity of subclinical CVD (all p > .05). Conclusion: In a large, multi-ethnic population with NAFLD, IL-6 is independently associated with the prevalence and severity of subclinical atherosclerosis. Further research into the longitudinal effects of NAFLD on progressive CVD will determine whether IL-6 is a marker or mediator of NAFLD-related atherosclerosis.